FORMATION OF STUDENTS’ CAREER ORIENTATION IN MODERN CONDITIONS: PROGRESS AND RESEARCH RESULTS - Ohrimenko, Zorina (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article describes the course and results of a study on the formation of career orientation among students in modern conditions. The aim of the article is to present the research process and findings in the context of forming students’ career orientation in modern conditions. To achieve this aim, the following tasks were addressed: to analyze scientific and methodological literature relevant to the research topic; to clarify the content and structural components of the concept of “students’ career orientation”; to present interim and final results of the study on the formation of students’ career orientation in modern conditions; and to substantiate a technology for forming students’ career orientation. To accomplish the goal and objectives, theoretical methods (analysis, synthesis, comparison, generalization, and systematization); empirical methods (interviews, surveys (questionnaires), testing, expert assessment, observation); and statistical methods for data processing and generalization were employed. The introduction outlines several objective factors that actualize the importance of forming students’ career orientation in the 9-10 grades of general secondary education institutions. It is emphasized that in the conditions of the New Ukrainian School reform, there is a problem with students’ conscious approach to an individual educational and professional trajectory. This includes equipping students with the knowledge and skills necessary for planning a professional career path in a dynamic and uncertain labour market, enhancing reflective processes (self-knowledge, self-awareness, self-efficacy), and stimulating the motivational value sphere of the personality. The essence of the term “students’ career orientation” is clarified, and its structure is presented. The study results on the levels of career orientation development among students at the diagnostic and formative stages of the research are provided. Based on Career Construction Theory (by M. Savickas), it is determined that the content of career orientation development for students should be aimed at acquiring knowledge and skills for planning a professional career path in a dynamic and uncertain labour market, enhancing reflective processes (self-knowledge, self-awareness, self-efficacy), and activating the motivational-value sphere of the personality. The article outlines the essence and demonstrates the effectiveness of technology for developing career orientation in students within the New Ukrainian School framework as a mechanism for shaping a system of attitudes toward individual educational and career trajectories. This system is built on a foundation of motives, personal meanings, and goals that continuously develop and motivate the individual toward self-development. The article’s practical significance is that its materials can be used in the professional orientation process of teenagers and high school students in senior specialized schools.